Buyang Huanwu Decoction Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Rats via Downregulation of Related Protein and Gene Expression. (28th February 2018) - Wang, Xuan; Li, Xia; Wang, Li-na; Pan, Jing-juan; Yang, Xue; Wei, Yang-lin
Abstract : Little is known about the effects of Buyang Huanwu decoction on pulmonary fibrosis. Herein, 144 healthy SD rats were randomly divided into six groups: blank control group (B), model control group (M), positive medicine control group (Mp), and high-, moderate-, and low-dose Buyang Huanwu decoction groups (Hd, Md, and Ld). A pulmonary fibrosis model was established by endotracheal injection of bleomycin. On the second day of modeling, the corresponding saline, methylprednisolone suspension, and the three doses of Buyang Huanwu decoction were used to treat the 6 groups of rats by intragastric administration for 7, 14, and 28 consecutive days. After 7, 14, and 28 days of treatment, the mRNA expression of CTGF and AKT, the protein level of CTGF, p-AKT, and collagen types I and III were tested. Finally, we found that the serum collagen type I and III level in Hd, Md, and Ld rats on the 14th and 28th day and the collagen type I and III level in Hd rats on 7th day were significantly lower than in M rats ( P < 0.01 ) . The protein level of p-AKT and CTGF in Hd and Md rats on the 7th and 14th days and the protein level of p-AKT in Hd rats on the 28th day were lower than in M rats (P < 0.01, P < 0.0 5 ). The level of CTGF mRNA in Hd, Md, and Ld rats and the level of AKT mRNA in Hd and Md rats on the 7th, 14th, and 28th days and the expression level of AKT mRNA in Ld rats on the 14th and 28th days were significantly lower than in M rats ( P < 0.01 ) . The study suggests that Buyang Huanwu decoction alleviated pulmonary fibrosis of rats by improvement of lung tissue morphology, low level of serum collagen types I and III, and the reduced expression of CTGF and p-AKT protein, which might be a result of its downregulated expression of CTGF and AKT mRNA levels.